FRACTION ANALYSIS OF SEDIMENT IN SELAT PADANG OF SUNGAI PAKNING RIAU PROVINCE - Hamidah Dasno Vera; Rifardi Rifardi; Elizal Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted in January-February 2019. To determine the types of sediment constituents material and the environmental conditions of the Selat Padang waters based on the texture of surface sediment. The sediment was taken using grab sampler from three station, in which each station consists of three sampling point. The results showed that sediment types were in the waters of the Selat Padang indomination by sandy mud.Sediment parameters in the Selat Padang have an average diameter (Mz) of 5.2-5.33 Ø with the classification of medium silt, sortingthat is2.16-2.93 Ø with the classification is the disaggregated very bad, skewness (-0.12)-(- 0.48) Ø with classification very rough, kurtosis is 4.80 - 25 Ø with the classification very sharp once classified into platikurtik .The sediment compositions found were lithogeneous and biogeneous dominated bylithogenous, indicate the sediment comes from coastal erosion carried by ocean currents and then deposited in the bottom of the watersThe highest average value of organic materials contained in the station 1 (12.76%) located in Sei Selari port which is included in the classification of the medium organic matter indicate little supply of organic material from the sea to the coast. Keywords: Selat Padang, Sediment, Sediment Composition, Organic Material